2021
DOI: 10.1128/msystems.01040-21
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Responses of Rare and Abundant Microbial Taxa to In Situ Chemical Stabilization of Cadmium-Contaminated Soil

Abstract: Understanding the ecological roles of rare and abundant species in the restoration of soil ecosystem functions is crucial to remediation of heavy metal-polluted soil. Our study assessed the efficiencies of five commonly used soil amendments on recovery of ecosystem multifunctionality and emphasized the relative contributions of rare and abundant microbial communities to ecosystem multifunctionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 80 publications
3
19
1
Order By: Relevance
“…Although the alpha diversity seemed more stable in the rare community, greater community dissimilarity (beta diversity) and more contributions to the overall community dissimilarity after perturbations than that of the abundant community were observed. These results agree with the findings of other studies in which the rare bacterial community was more sensitive to environmental changes than the abundant bacterial community in the beta diversity dimension ( 27 ). The sensitivity of the rare taxa could be explained by their narrow environmental breadths to environmental changes ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although the alpha diversity seemed more stable in the rare community, greater community dissimilarity (beta diversity) and more contributions to the overall community dissimilarity after perturbations than that of the abundant community were observed. These results agree with the findings of other studies in which the rare bacterial community was more sensitive to environmental changes than the abundant bacterial community in the beta diversity dimension ( 27 ). The sensitivity of the rare taxa could be explained by their narrow environmental breadths to environmental changes ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, most of these bacterial keystone taxa were rare species, whereas the only fungal keystone identified was an abundant species. Indeed, a growing number of studies have highlighted the key role that rare species play in maintaining microbial community structure ( Power et al, 1996 ; Xu et al, 2021 ; Zhu et al, 2021b ). Generally, rare taxa of bacteria are highly active, as indicated by higher 16S rRNA/rRNA genes, and can increase rapidly under changing environments ( Campbell et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of sensitivity of rare species to abiotic changes caused by the fact that these rare species are neither opportunistic nor take advantage of the reduction of dominant species may be the reason why rare species become the majority of keystones ( Kurm et al, 2019 ). Notably, most rare bacterial species and abundant fungal species as keystone taxa that played important roles in maintaining the stability of intra-kingdom microbial co-occurrence networks have also been reported in cadmium-contaminated soil, but whether or not this phenomenon was random requires further study ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar treatments may have little effect on the distribution and reconstructing the abundant and rare fungal taxa in the soil. Studies have shown that the rare microbial taxa can act as a microbial seed bank to safeguard the entire community ( Dong et al, 2021 ; Xu et al, 2021 ). Our results demonstrated that the rare bacterial taxa (such as cyanobacteria ) get activated by biochar, and thus maintained the bacterial community stability under pollution stress, which was not the case in the group with no biochar application.…”
Section: Discussionmentioning
confidence: 99%